CONJUNCTIVITIS CAUSED BY CHLAMYDIA BACTERIA ACCOMPANIED BY DIARRHEA DUE TO TOXOCARA CATI AND ISOSPORA FELIS OOCYSTS IN DOMESTIC CAT - Mawar Datu Allo Dendang; Sri Kayati Widyastuti; I Nyoman Suartha (Buletin Veteriner Udayana, 2024)
Conjunctivitis is an eye disorder where inflammation occurs in the conjunctival tissue that lines the eye. Chlamydia felis is a frequent cause of infection in cats which usually causes conjunctivitis in kittens. One of the diseases that often attacks cats' digestion is diarrhea which can be caused by worms. A 2 month old domestic cat, body weight 0.5 kg, white-orange hair, mucopurulent discharge, swelling and red mucosa in both eyes. The case cat had diarrhea, the feces were blackish green and contained a little blood. The results of the eye fluid cytology test found chlamydia bacteria and fecal examination found Toxocara cati worm eggs and Isospora felis oocysts. The test kit examination showed negative Feline Panleukopenia Virus (FPV) and the results of the Complete Blood Cell examination showed leukocytosis and thrombocytopenia. Based on the history, physical examination and supporting examinations, the case cat was diagnosed as suffering from conjunctivitis caused by chlamydia bacteria accompanied by diarrhea due to Toxocara cati and Isospora felis oocysts with a fausta prognosis. The treatment given is antibiotics and anti-inflammatories for conjunctivitis (dexametasone and chloramphenicol), anti-parasitic and digestive antibiotics (metronidazole), anti-diarrhea (kaolin pectin), worm medicine (pyrantel pamoate), and Livron B.plex® supplements. The case cat showed an improved condition after 14 days of treatment, namely there was no mucopurulent discharge in both eyes, the eye mucosa returned to normal, and there was no swelling in the eyes, no Toxocara cati worm eggs and Isospora felis oocysts were found, normal feces (not liquid, not slimy). , no blood, brownish). Based on the history, physical examination, and supporting examinations on the case cat, it was diagnosed as suffering from conjunctivitis caused by Chlamydia bacteria accompanied by diarrhea due to Toxocara cati and Isospora felis oocysts. It is necessary to pay attention to the cleanliness of the environment where cats live to avoid infections in the future, avoid cats playing in sandy or dirty places and the food they give must also be considered.